Evaluasi Critical Success Factors Pada Implementasi Sistem Informasi Supply Chain Management (ALISTA) Menggunakan Metode Dematel Pada PT. Telkom Akses Malang - Nina Dian Kusumawardani; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Supply Chain Information System in PT. Telkom Akses or known as ALISTA is a website-based information system that helps PT. Telkom Akses to manage its supply chain. Nevertheless, practically, PT. Telkom Akses especially in Malang have many obstacles within the implementation. This study aims to evaluate CSF in implementation of ALISTA. The speakers in this study consisted of 5 stakeholders in ALISTA who are the IT Support staff, Team Leader Operational, Team Leader Procurement, Team Leader Finance and General Manager. The method used in this study is DEMATEL method. The calculation result using the DEMATEL method shows several factors that have the highest degree of prominence, namely communicating effectively (CSF001) with value of 0.643, managing relationships (CSF002) with value of 0.563 and align vision and build plans (CSF005) with value of 0.556. There are also factors that have a large influence (degree of relation) on other factors, namely taking top management responsiveness (CSF004) with value of 0.177, align vision and build plans (CSF005) with value of 0.110 and communicate effectively (CSF001) with value of 0.037. Factors with high importance and still not well implemented, such as CSF001, CSF004 and CSF005 need to be considered more optimally to achieve 80% success in implementing ALISTA.